A Case of Systemic Severe Bullous Pemphigoid Caused by Long-Term Sintilimab Treatment for Renal Cell Carcinoma - He J; Duan X; Liu T; Yang H; Jiang J; Mu Y (Dove Medical Press, 2022)
Jia He, Xi Duan, Ting Liu, Hao Yang, Jingjing Jiang, Yunzhu Mu Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, Nanchong, People's Republic of ChinaCorrespondence: Yunzhu Mu, Department of Dermatology, Affiliated Hospital of North Sichuan Medical College, No. 1 Maoyuan South Road, Shunqing District, Nanchong City, Sichuan Province, 637000, People's Republic of China, Tel +8615983785601, Email hymyz@126.comAbstract: Immune-related adverse events have been reported in relation to programmed cell death protein-1 (PD-1). However, there are few reports on PD-1 inhibitor-induced bullous pemphigoid. We report the case of a patient who developed bullous pemphigoid following long-term administration of sintilimab for renal cell carcinoma. He developed scattered erythema, blisters, and generalized pruritus for 1 week before admission. Histopathology showed subepidermal blisters and direct immunofluorescence showed linear deposition of immunoglobulin G and complement 3 on the basement membrane; the level of BP180 was 146.93U/mL. A regimen containing methylprednisolone, minocycline, and niacinamide was administered and the patient was discharged following resolution of symptoms.Keywords: bullous pemphigoid, PD-1, PD-L1, sintilimab